Improving the drinking water supply system in the capital of Tomia Timur Subdistrict, Tomia Island, Wakatobi Regency - Sukardin, Sukardin; Aswad, Nini Hasriyani; Kadir, Abdul (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
This research aims to improve the Municipal Drinking Water Supply System (SPAM IKK) in East Tomia, Wakatobi Regency, using a combined method approach and involving 76 participants. The findings indicate that water services in East Tomia adhere to the 4K principles (Quantity, Quality, Continuity, and Accessibility), with an increase in water volume despite some distribution challenges. Water quality remains high due to regular testing, and continuous service is ensured through ongoing maintenance, making the service accessibility for the community. Strategic improvements over the next 5-10 years include the implementation of solar-powered pumps, expansion of storage infrastructure, and enhancement of the distribution system to improve efficiency and sustainability. Recommendations include infrastructure upgrades, adoption of green technology, consistent quality checks, and support from proactive local government policies.